Tajeu: The boy born into drought - International Livestock Research Institute (International Livestock Research Institute, 2012)
This story tells of the hopes of a Maasai pastoralist from Kenya's Kitengela rangelands and his dreams for his son Tajeu, who was born during a devastating drought.